2022
DOI: 10.4244/eij-e-21-00009
|View full text |Cite
|
Sign up to set email alerts
|

2021 ESC/EACTS Guidelines for the management of valvular heart disease

Abstract: The ESC Guidelines represent the views of the ESC and were produced after careful consideration of the scientific and medical knowledge and the evidence available at the time of their dating. The ESC is not responsible in the event of any contradiction, discrepancy and/or ambiguity between the ESC Guidelines and any other official recommendations or guidelines issued by the relevant public health authorities, in particular in relation to good use of health care or therapeutic strategies. Health professionals a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
581
1
41

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 548 publications
(879 citation statements)
references
References 598 publications
6
581
1
41
Order By: Relevance
“…In this scenario, AVI serves mainly as prophylaxis in the treatment of moderate AR to avoid repeat open-heart surgery. This indication remains controversial in 2021 ESC/EACTS guidelines, as previous small single-center data showed that the progression of moderate AR is slow and indolent ( 6 , 23 ). However, a recent large-sample investigation of the natural history of AR showed that the 10-year incidence of progression to stage C/D AR was 53.4% among patients with moderate AR (median 2.96 [1.2–5.4] years), in contrast to those with trivial/mild AR (11.7%, HR = 4.71) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, AVI serves mainly as prophylaxis in the treatment of moderate AR to avoid repeat open-heart surgery. This indication remains controversial in 2021 ESC/EACTS guidelines, as previous small single-center data showed that the progression of moderate AR is slow and indolent ( 6 , 23 ). However, a recent large-sample investigation of the natural history of AR showed that the 10-year incidence of progression to stage C/D AR was 53.4% among patients with moderate AR (median 2.96 [1.2–5.4] years), in contrast to those with trivial/mild AR (11.7%, HR = 4.71) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a common indicator of LVSD, reduced LV ejection fraction (LVEF) <50 or 55% is known to be a potent predictor of poor prognosis and serves as a reasonable indication for aortic valve intervention (AVI) in patients with severe AR ( 6 , 7 ). However, the prognostic value of LVEF and its best cutoff for risk prediction in patients with moderate AR remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main groups of bioprosthetic surgical valves: stented and stentless surgical devices [13,14] . Stentless valves, representing approximately 20% of patients with ViV, most frequently present with regurgitation as a modality of degeneration, with lower postprocedural gradients than those observed with stented valves but with higher rates of periprocedural complications as initial device malposition, second transcatheter device, coronary obstruction and paravalvular leak, but no difference in 30-day and 1-year outcome [7] . Stented valves, especially those with externally mounted leaflets (e.g., Mitroflow, Livanova PLC/Sorin Group, Saluggia, Italy), have frequently been used in the past, mainly in small anatomies, because they guarantee a lower final gradient, but these are the valves at the highest risk for coronary obstruction in ViV procedures [15,16] .…”
Section: Bioprosthetic Valve Characteristicsmentioning
confidence: 98%
“…Among the hypotheses evaluated, it appears that this complication may result from design factors [87] . Therefore, a more aggressive anticoagulation regimen after ViV TAVR is recommended, especially in patient with high thrombotic risk and low hemorrhagic risk [7] .…”
Section: Post-implant Valve Thrombosismentioning
confidence: 99%
See 1 more Smart Citation